Neuroscientific evidence for pain being a classically conditioned response to trauma- and pain-related cues in humans - Franke, Laila K.; Miedl, Stephan; Danböck, Sarah K.; Grill, Markus; Liedlgruber, Michael; Kronbichler, Martin; Flor, Herta; Wilhelm, Frank H. (Pain, 2022)
Psychological trauma is typically accompanied by physical pain, and posttraumatic stress disorder (PTSD) often cooccurs with chronic pain. Clinical reports suggest that pain after trauma may be part of re-experiencing symptomatology. Classical conditioning can underlie visual re-experiencing because intrusions can occur as conditioned responses (CRs) to trauma-related cues. If individuals also experience pain to cues previously paired with, but not inflicting nociceptive stimulation anymore (ie, conditioned stimuli, CS), conditioning could also explain re-experiencing of pain. Sixty-five participants underwent classical conditioning, where painful electrocutaneous stimulation and aversive film clips served as unconditioned stimuli (US) in a 2 (pain/no pain) × 2 (aversive/neutral film) design. Conditioned stimuli were neutral pictures depicting contextual details from the films. One day later, participants were re-exposed to CS during a memory-triggering task (MTT). We assessed pain-CRs by self-report and an fMRI-based marker of nociceptive pain, the neurological pain signature (NPS), and recorded spontaneous daily-life pain intrusions with an e-diary. During conditioning, pain-signaling CS elicited more self-reported pain and NPS responses than no-pain-signaling CS. Possibly because the aversive film masked differences in participants' responses to pain-signaling CS vs no pain-signaling CS, pain-CRs during acquisition were most evident within the neutral film condition. When participants were re-exposed to CS during MTT, self-reported pain-CRs during the neutral film condition and, although more uncertain, NPS-CRs during the aversive film condition persisted. Of importance, participants with stronger pain-CRs showed a greater probability and severity of experiencing spontaneous pain intrusions during daily life. Our data support that spatiotemporally associating innocuous cues with pain (CS) endows these cues to elicit conditioned pain responses in the absence of noxious stimulation. In this way pain can emerge as a CR with emotional and sensory components. Classical conditioning presents a possible mechanism explaining pain intrusions and, more broadly, pain experienced without a nociceptive input.
Gesehen am 12.06.2023